Formation of Global Competence and Character through International Field Studies based on Islamic Educational Values - Rosmita Zaynarriyah; Rosnani Siregar (International Tatho Academics, 2026)
This study aims to describe the implementation of a field study to Universiti Utara Malaysia (UUM), to analyze its contribution to enhancing students’ competencies and international outlooks, and to reflect on the internalization of tarbiyah Islamiyah values in the learning process. The method employed is a descriptive qualitative approach through field observations, activity documentation, and students’ academic reflections during the field study. The findings indicate that the field study activities provided contextual learning experiences that enriched students’ understanding of international higher education systems, academic culture, and university governance. Students experienced improvements in academic competence, communication skills, teamwork, adaptive attitudes, and global mindset. In addition, the internalization of Islamic values such as discipline, responsibility, academic etiquette, and openness to cultural differences was fostered throughout the activities. This study’s contribution emphasizes international field studies grounded in Islamic educational values are effective as a means of strengthening competencies and shaping students’ global character.